Islamic religiosity measurement and its relationship with business income zakat compliance behavior (Ukuran nilai keagamaan dalam Islam dan hubungannya dengan gelagat kepatuhan zakat perniagaan) - Kamil Md Idris; Zainol Bidin; Ram Al Jaffri Saad (Penerbit Universiti Kebangsaan Malaysia, 2012)
Quantitative Islamic religiosity measuremet and its related studies are hardly found in literature. As a result, many researchers have used the conventional measurements which are derived from the west. The suitability of these measurements in Islamic environment is questionable. Thus, the purpose of this study is to examine the quantitative Islamic religiosity mesurement from the Islamic perspective and to determine whether the composition of these measurement associates are in compliance with the behavior of zakat. A survey was carried out on 227 repondents. results indicate that the business owners who are highly religious are also more likely to comply with zakat law. Thus, this study concludes that religiosity measurement from Islamic perpective is as complex as the conventional ones and it is composed of several dimensions. It also suggests that religiosity plays an important role in zakat compliance behavior.